HISTOLOGICAL CHANGES IN THE SMALL INTESTINE IN THE ADVANCED STAGES OF BURN DISEASE - Галунко, Г.М. (World of Medicine and Biology, 2017)
The maximum level of degeneration in the epithelial cells of the intestinal villi and endothelial cells of the vessels in the small intestine wall histological level manifested after 14 days from the beginning of the experiment. 30 days after the burn injury of the skin, the degenerative and destructive changes, as well as the areas of desquamation of the intestinal epithelium of the intestinal villi, are less pronounced than in the previous study periods. However, despite the fact that the number of hemorrhages and their size, the swelling of the connective tissue and the number of lymphocytes in the submucosal wall of the ileum were less than in the previous study period, the listed events were more pronounced than in the non-burning rats, which during the first seven days 0.9% solution of NaCl was injected at a dose of 10 ml per kg, which prompted us to pursue the search for more effective means.